Boundary feedback stabilization of the telegraph equation: Decay rates for vanishing damping term - Gugat, Martin (Systems & Control Letters, 2014)
We study a semilinear mildly damped wave equation that contains the telegraph equation as a special case. We consider Neumann velocity boundary feedback and prove the exponential stability of the closed loop system. We show that for vanishing damping term in the partial differential equation, the decay rate of the system approaches the rate for the system governed by the wave equation without damping term. In particular, this implies that arbitrarily large decay rates can occur if the velocity damping in the partial differential equation is sufficiently small. © 2014 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dma.lama1.bounda
Keywords: Anti-damping; Boundary feedback; Damping; Decay rate; Exponential stability; Hyperbolic partial differential equation; Nonlinear wave equation; Semilinear wave equation; Telegraph equation